Successful Use of Kidneys from a Deceased Donor with Active Herpes Zoster Infection. (16th August 2021) - Vinson, Amanda J.; Chauhan, Prakash; Daley, Christopher; De Silva, Himanthi; Tennankore, Karthik K.; Bonnar, Paul; West, Kenneth A.
Abstract : Background . The limited donor pool and increasing recipient wait list require a reevaluation of kidney organ suitability for transplantation. Use of higher infectious risk organs that were previously discarded may help improve access to transplantation and reduce patient mortality without placing patients at a higher risk of poor posttransplant outcomes. There is very little data available regarding the safe use of kidney organs from deceased donors with varicella zoster virus infection at the time of organ retrieval. Case Presentation . Here, we report a case of successful transplantation of both kidneys from a deceased donor with active herpes zoster infection at the time of organ retrieval. Recipients were treated preemptively with acyclovir. At 4 months posttransplant, both kidney recipients experienced no infectious complications and were off dialysis with functioning transplant grafts. Conclusions . The use of kidney organs from donors with active herpes zoster infection appears to be a safe option to expand the kidney donor pool.